2023
DOI: 10.3390/diagnostics13162677
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prostate Volume on the Prostate Imaging and Reporting Data System (PI-RADS) in a Real-World Setting

Abstract: Multiparametric magnetic resonance imaging (mpMRI) has emerged as a new cornerstone in the diagnostic pathway of prostate cancer. However, mpMRI is not devoid of factors influencing its detection rate of clinically significant prostate cancer (csPCa). Amongst others, prostate volume has been demonstrated to influence the detection rates of csPCa. Particularly, increasing volume has been linked to a reduced cancer detection rate. However, information about the linkage between PI-RADS, prostate volume and detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, PV has an insignificant impact on the detection of csPCa in patients with PI-RADS 3 lesions when the cutoff value > 43.5 ccm in Volz's report. 12 So, further studies are still needed for quantitative analysis of PV. Previous studies have demonstrated ADC min value can help predict PCa aggressiveness.…”
Section: Studies On Psad In Western Populations Have Been Widelymentioning
confidence: 99%
See 1 more Smart Citation
“…However, PV has an insignificant impact on the detection of csPCa in patients with PI-RADS 3 lesions when the cutoff value > 43.5 ccm in Volz's report. 12 So, further studies are still needed for quantitative analysis of PV. Previous studies have demonstrated ADC min value can help predict PCa aggressiveness.…”
Section: Studies On Psad In Western Populations Have Been Widelymentioning
confidence: 99%
“…10 In addition, there are many reports the detection rate of PCa is related to the size of the prostate. 11,12 These variables have been shown to be useful in the diagnosis of PCa, but few reports have studied those variables alone for PI-RADS score 3 patients.…”
Section: Introductionmentioning
confidence: 99%